ANALISIS PENGARUH PENERAPAN TAX REVIEW ATAS PAJAK PERTAMBAHAN NILAI (PPN) PADA PT. âABCâ - Anitarahmi, Astrid (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
PT ABC has not used tax consultant service in carrying out its previous tax liability to examine theresult of tax report, but in 2013 before PT ABC carried out annual tax return report, the companyhired tax consultant service to review all of the companyâs tax reports to make it suitable with theprevailing tax regulation. This research is held with the purpose to analyze how the implementation oftax review and tax planning that has been carried out by the tax consultant of PT ABC to the wholetax liabilities of the company particularly on the value-added tax (PPN) in which some differences inthe magnitude of the amount of value-added tax between the calculation that has been performed bythe employees of PT. ABC and tax consultant. Tax review that has been conducted is very useful tominimize all of the risk that has been caused by the error in the calculation of its tax liabilities.Keywords: Tax, Value-added Tax (PPN), Tax Review, Tax Planning.